ОБРАЗ ЖИВОТНОГО И КУЛЬТУРНЫЕ УНИВЕРСАЛИИ - Jaworska-Bendyk, Karolina (Acta Neophilologica, 2018)
As material for this research we used the phraseological units containing zoonym ‘dog’. Zoonyms are complex language units which have a great linguistic potential. Our aim was to reveal the metaphorical potential of cultural concept ‘dog’, and to analyse characteristics of concept, in order to answer the question – can concept ‘dog’ be treated as universal category of culture.